Implications of the Cost of Equity in Corporate Valuations : Practical applications challenging financial theory - Tolonen, Joonas (My University, 2020)
In the most distinctive valuation method DCF, the first letter stands for discount rate, and as such has a major impact on the EVs obtained using the model. The discount rate is typically determined by estimating a weighted average cost of capital, comprised of two different costs, the cost of equity and the cost of debt. The prior being a more controversial figure which requires consideration. While many aspects in financial theory and practices have been standardized over time, the determination of the cost of equity can still be performed using various models and inputs. Even though financial literacy has provided multiple asset pricing models that should better the CAPM, due to practical difficulties the latter, or a version of it, is still favored by most practitioners. However, even though practitioners commonly agree that the CAPM is a generally accepted model, the premiums included in the model may vary from practitioner to another. The purpose of this thesis is to examine the following considerations: Can the CAPM be utilized in company valuations? Do valuations of small private companies require pricings of unsystematic risks? How do practical approaches diverge from theory? Do theoretical frameworks enhance practical valuations? While estimating the cost of equity for private valuations, the modified CAPM is the most applied asset pricing model. The model typically includes at least three standard inputs, the risk-free rate, the beta factor, and the equity risk premium. In addition, most models commonly include at least one unsystematic component, a size premium, while some also incorporate a country risk premium. The latter being a risk that divides both academics and practitioners on whether it is diversifiable or not. The empirical evidence of the study in this thesis is gathered by interviewing four experienced corporate finance professionals by the means of semi-structured interviews. The findings of this study are quite consistent with prior research reviewed. Regardless, of its shortcomings, all interviewees support the usage of a modified CAPM. Furthermore, it is found that the modified CAPM can be utilized to determine the cost of equity, as long as the model also considers unsystematic components. While theoretical frameworks are important, the practices applied by the interviewees do diverge traditional foundations.

Tunnistetuimmassa arvonmääritysmenetelmässä DCF ensimmäinen kirjain tarkoittaa diskonttokorkoa. Tällä korolla on suuri vaikutus menetelmän lopputulokseen. Diskonttokorko tyypillisesti määritetään arvioimalla pääoman keskimääräinen kustannus, mikä muodostuu kahdesta eri pääoman kustannuksesta, oman pääoman kustannuksesta ja vieraan pääoman kustannuksesta. Näistä ensimmäinen on kiistanalainen estimaatti, ja täten vaatii huomiota. Siinä missä moni seikka sekä kirjallisuudessa että käytännössä on kyetty standardisoimaan, oman pääoman kustannus voidaan edelleen määrittää vaihtoehtoisilla malleilla ja komponenteilla. Vaikka teoriat ovat tuottaneet monia estimointimalleja, joiden pitäisi tuottaa parempia tuloksia kuin CAPM, käytännön yleistettävyysongelmien johdosta versio CAPM:ista on edelleen asiantuntijoiden suosiossa. Siltikin vaikka asiantuntijat ovat yksimielisiä siitä, että CAPM on yleisesti hyväksytty malli, malliin sisällytettävät preemiot vaihtelevat asiantuntijasta toiseen. Tämän tutkielman tarkoitus on käsitellä seuraavia harkintoja: Voiko CAPM:ia käyttää yritysten arvonmäärityksissä? Vaativatko pienyhtiöiden arvonmääritykset epäsystemaattisia komponentteja? Miten käytännön mallit eroavat teoriasta? Edistävätkö teoreettiset kehykset käytännön arvonmäärityksiä? Oman pääoman kustannuksen määrittämisessä modifioitu CAPM on suosituin arviointimalli. Malli sisältää tyypillisesti ainakin kolme traditionaalisesta komponenttia, riskittömän koron, betan, ja markkinariskipreemion. Näiden lisäksi monet mallit usein sisältävät myös ainakin yhden epäsystemaattisen tekijän, kokopreemion. Lisäksi toiset saattavat sisällyttää myös maariskipreemion, jonka hajauttamismahdollisuudet jakaa sekä akateemikot että asiantuntijat. Tämän tutkielman tutkimuksen empiiriset havainnot on kerätty haastattelemalla neljää asiantuntijaa. Tutkimusmenetelmäksi on valittu teemahaastattelut. Tutkimuksen tulokset ovat hyvin johdonmukaiset suhteessa aikaisempiin tutkimuksiin. CAPM:in heikkouksista huolimatta kaikki haastateltavat tukevat modifioidun mallin käyttöä. Tutkimus toteaa, että modifioitua CAPM:ia voidaan hyödyntää oman pääoman kustannuksen määrittämisessä, sillä ehdolla että malliin sisällytetään myös epäsystemaattisia tekijöitä. Vaikka teoreettisia kehyksiä pidetään arvostuksessa, asiantuntijoiden hyödyntämät mallit eroavat osittain teoriasta.
Keywords: the cost of equity, beta, premium, CAPM, estimation, practice, theory